Pembuatan Media Tanam Hidroponik Dengan Sistem Irigasi Otomatis Berbasis IoT - M. Qoyum Zuhriawan; Faisol Hidayatulloh; Iin Baroroh Ma'arif; Suci Prihatiningtyas; Wulan Amalia Devi (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Hydroponic planting media is a planting system that does not use soil to grow plants, instead it can use water. Many people already use hydroponic media but there is more effort to monitor the planting process, this is a new obstacle to the hydroponic system. Therefore, to support the hydroponic planting system to make it more efficient, this Pkm has a theme of IOT Based Irrigation. The location of this Pkm is in Kedunglumpang Village, Mojoagung subdistrict, Jombang district. Pkm participants include farmers, PKK, IPNU, and IPPNU. The result of this Pkm is that the majority of local people are familiar with hydroponic but do not understand the implementation process. Then, after attending the training, many people were enthusiastic about making hydroponic media using IoT technology in their yards.